Administrative Tolerance and Tax Revenue: A Synergistic Desparity - OJONG, OBEN VALENTINE; EFFIONG, SUNDAY A. (The journal of contemporary issues in business and government, 2021)
Raising sufficient tax revenue is one of the main objectives of all governments at any given moment. Thus, any policy that goes in this direction and which does not undermine or compromise the rule of law and threatens the sustainability of the government is a welcome initiative. It is in this light that ‘administrative tolerance’ saw the light of the day in Cameroon’s public administrative land scape. The problem of this phenomenon today is that, the initial basis on which it was introduced, currently threatens its existence due to corruption and selfishness of some administrative officials in both public and private organizations. This study aimed at examining the effect of the synergy between administrative tolerance implementation and tax revenue, on a sectorial basis. The expo- facto research design was used since the data for the study were secondary, and a model was developed to suit the objective of the study. The data were analysed using SPSS Version 23.0 with the use of multiple regression model. The results revealed that Administrative Tolerance manifests a synergistic desparity with Tax Revenue over the period of the study, using the three proxies of Private Secondary School Enrolments as a percentage of Total Secondary School Enrolments, Commercial Services Exports measured at current US dollars and percentage Fuel Export as a percentage of Total Merchandise Exports. Therefore, it was observed from the study that Administrative Tolerance on the Private Secondary Education sector has a significant positive effect on Tax Revenue, while any such tolerance on Commercial Services Exports and Fuel Exports negatively affected Tax Revenue. This study recommends that the government should have a framework for Administrative Tolerance in which specifics on when and how or the extent of such tolerance to each particular sector. A blanket policy should not be used at any given period on all sectors as this may result in negative effects on Tax Revenue.